Pendidikan Islam dan Perubahan Iklim: Respons Qur’ani-Hadis terhadap Krisis Lingkungan Kontemporer - Budi Agung; Lil Sapnur Aspin Siregar (Yayasan Albahriah Jamiah Indonesia, 2025)
Climate change is one of the most pressing environmental crises facing the world today, with far-reaching social, economic, and ecological impacts. In the context of Islamic education, there is an urgent need to integrate the teachings of the Qur’an and Hadith as a moral and ethical basis for addressing this environmental crisis. This article aims to explore how Islamic education can provide an effective response to climate change from the perspective of the teachings of the Qur’an and Hadith. The research method used is qualitative and analysis of religious texts with a literature approach, combining interpretations of the verses of the Qur’an and Hadith related to nature conservation, human responsibility as caliphs, and the principle of ecological justice. The results of the study show that Islamic teachings explicitly encourage ecological awareness, sustainable management of natural resources, and the obligation to maintain the balance of Allah’s creation. Islamic education can play a strategic role in shaping ecological attitudes and behaviors based on spiritual values ​​and environmental ethics. In conclusion, the integration of the teachings of the Qur’an and Hadith in Islamic education is not only relevant but also essential as a response to the climate change crisis, which can inspire real action in environmental conservation and sustainable development. This approach is the foundation for the formation of a generation that cares about the environment, according to religious guidance.